Church, State, and Original Intent - Hitchcock, James (A journal of church and state, 2010)
Almost inevitably, the author approaches his subject by quoting the famous Sherlock Holmes remark about the dog that did not bark. Noting that he once found the intentions of the Founding Fathers concerning church and state to be “unknowable,” Drakeman now argues that their very silence reveals their understanding of the Establishment Clause., For a long time, this has been the most baffling conundrum concerning the subject. Given the intensity of later battles over church and state, which show no sign of abating after more than two centuries, how is it that the clause “Congress shall make no law,” was approved with almost no debate, except over refinements of language.